Comparison of transthoracic echocardiography with harmonic imaging with transoesophageal echocardiography for the diagnosis of patent foramen ovale - Trevelyan, J (BMJ Group, 2006)
The optimal diagnostic method for patent foramen ovale is currently unclear. This study compared bubble contrast second harmonic transthoracic (TTE) and transoesophageal echocardiography (TOE) on 87 consecutive patients referred for TOE for all indications. A right left shunt was diagnosed in 34 cases (39%), with TTE positive in 26 cases (sensitivity 76.5%), TOE positive in 27 cases (sensitivity 79.4%). Pitfalls of TTE included quality of echo and left sided valve lesions, and for TOE the ability to perform an adequate Valsalva manoeuvre. In conclusion, both tests have similar sensitivity and should be viewed as complementary modalities.